Gait training in orthopedic rehabilitation after joint replacement - back to normal gait with sonification? - Pietschmann, J.; Geu Flores, F.; Jöllenbeck, T. (International Journal of Computer Science in Sport, 2019)
Even several years after total hip (THR) and total knee replacement (TKR) surgery patients frequently show deficient gait patterns leading to overloads and relieving postures on the contralateral side or in the spine. Gait training is, in these cases, an essential part of rehabilitation. The aim of this study was to compare different feedback methods during gait training after THR and TKR focusing, in particular, on auditory feedback via sonification. A total of 240 patients after THR and TKR were tested in a pre-post-test design during a 3-week rehabilitation period. Even though sonification did not show, statistically, a clear advantage over other feedback methods, it was well accepted by the patients and seemed to significantly change gait pattern during training. A sudden absence of sonification during training led to a rapid relapse into previous movement patterns, which highlights its effectiveness in breaking highly automated gait patterns. A frequent use of sonification during and after rehabilitation could, hence, reduce overloading after THR and TKR. This may soon be viable, since new technologies, such as inertial measurement units, allow for wearable joint angle measurement devices. Back to normal gait with sonification seems possible.